2013
DOI: 10.1063/1.4817017
|View full text |Cite
|
Sign up to set email alerts
|

Compressional Alfvénic rogue and solitary waves in magnetohydrodynamic plasmas

Abstract: Generation of compressional Alfvénic rogue and solitary waves in magnetohydrodynamic plasmas is investigated. Dispersive effect caused by non-ideal electron inertia currents perpendicular to the ambient magnetic field can balance the nonlinear steepening of waves leading to the formation of a soliton. The reductive perturbation method is used to obtain a Korteweg–de Vries (KdV) equation describing the evolution of the solitary wave. The height of a soliton is proportional to the soliton speed “U” and inversely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…amount of energy accumulated in a small region makes the oscillations much stronger than the surrounding waves, with the initial process forming rogue waves usually attributed to the modulational instability. In the context of plasma physics, rogue waves have been studied for both electrostatic [44][45][46] and electromagnetic [47][48][49] modes. Shukla and Moslem [47] studied the formation of left-and right-hand circularly polarized Alfvénic rogue waves due to the nonlinear interaction between circularly polarized dispersive Alfvén waves and lowfrequency electrostatic perturbations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…amount of energy accumulated in a small region makes the oscillations much stronger than the surrounding waves, with the initial process forming rogue waves usually attributed to the modulational instability. In the context of plasma physics, rogue waves have been studied for both electrostatic [44][45][46] and electromagnetic [47][48][49] modes. Shukla and Moslem [47] studied the formation of left-and right-hand circularly polarized Alfvénic rogue waves due to the nonlinear interaction between circularly polarized dispersive Alfvén waves and lowfrequency electrostatic perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Panwar et al [48] studied the Alfvén rogue and solitary waves in an MHD plasma. It was shown that compressional solitons exist, and the amplitude of the solitons increases with increasing soliton speed and decreases with the plasma β.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 An important mathematical model for the rogue wave is the rational solution of the nonlinear Schr€ odinger (NLS) equation in the unstable region. The features of rogue waves have been theoretically investigated in many plasma systems [31][32][33][34][35][36][37][38] and confirmed in experiments. 39,40 The aim of this paper is to investigate the propagation of rogue waves in an ion-beam plasma containing negative ions, positive ions, and superthermal electrons with a kappa-type distribution.…”
Section: Introductionmentioning
confidence: 96%
“…Theoretically, rational solutions of nonlinear Schrödinger (NLS) type systems play a major role in the study of rogue waves for deep water. Rogue waves appear also in many other physical fields where the NLS type systems can be used, especially in nonlinear optics [6,7], plasmas [8,9], atmosphere [10,11], Bose -Einstein condensations (BECs) [12] and financial problems [13].…”
mentioning
confidence: 99%